Komunikasi Sosial (melalui Smartphone) sebagai Sumber Informasi Seksual: Ancaman bagi Kesehatan Reproduksi Remaja - Partini Partini (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Smartphones and Gadgets are reliable, cheap and easy media for the youth in their search for information on sexuality and reproductive health related issues in the Millennium era. The youths at their adolescent age have not yet acquired sufficient knowledge to differentiate between right and wrong, which makes them vulnerable to the practice of trying and emulating new things that come their way. One such tendency is the prone of the youth to pre marital sex. Sex and Sexuality are no longer taboo, but on the contrary have become commodities, a problem that underscores the importance of education about sex and reproductive health. The family, which should be the bedrock on this, lacks sufficient knowledge necessary to play its role. The conveyance process is bedeviled by information, communication, and psychological gaps, which force the youths to make their own search for answers. The negative impact of all this is reflected in the rapid spread of HIV/AIDS, sexually transmitted diseases, KTD and abortion.